Biometric study of Italian population of Reticulitermes lucifugus Rossi (Isoptera Rhinotermitidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The replacement of reproductives population of the Reticulitermes Holmgr. gathered from various areas in Italy have been compared.Head, thorax and legs in 18 specimens were measured.The data have been statistically processed through variance analysis, Tukey's test, cluster analysis and principal components analysis.We have come to the conclusion that the species or subspecies santonensis Feyt. is not present in Italy and that the Italian population of R. lucifugus Rossi can be subdivided in two groups differing from a biometrie point of view.The first one includes colonies living in northern Italy, Rome and Sardinia; the second one includes only the colonies living in Palermo.
Keywords: Reticulitermes lucifugus; biometrie study; Italian termites